Psiko-Sufistik sebagai Ilmu Otonom: Menegaskan Identitas Keilmuan di Tengah Fragmentasi Ilmu: Penelitian - Wijaya (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This article discusses Psiko-Sufistik as an autonomous and independent scientific discipline in the context of the fragmentation of modern knowledge. Psiko-Sufistik is an integration between psychology and Islamic Sufism, which studies the human psyche through a spiritual-transcendental approach. This study aims to examine the epistemological and ontological foundations of Psiko-Sufistik, identify the characteristics of its scientific autonomy, and evaluate its contribution to addressing the fragmentation of knowledge. The research method used is qualitative literature study by analyzing relevant scholarly journals. The findings show that Psiko-Sufistik has a specific formal object, methodology, and terminology that qualify it as an autonomous science. This article also recommends the institutionalization of Psiko-Sufistik in the form of curriculum development and applicable therapeutic practices.